Multipurpose prevention technologies for reproductive and sexual health. Issue 44 (November 2014) - Stone, Alan
Abstract: Global statistics on unplanned pregnancies, abortions and STIs show that unprotected sex is still widely practised. More needs to be done to provide women and men with a wider choice of convenient protective options. To address this need, international efforts are focusing on developing multipurpose prevention technologies (MPTs) that address two or more indications simultaneously. These technologies would have significant advantages over single-indication products. They include inter alia novel barrier devices, drugs administered either as oral tablets or vaginal/rectal gels, drugs used in combination with medical devices, and genetically engineered organisms which secrete antimicrobial substances. As an example of progress in the MPT field, this paper describes an on-demand contraceptive/antimicrobial vaginal gel, Amphora (previously known as Acidform), now in an advanced stage of development. Clinical trials are currently being planned to find out whether this product's promising antimicrobial profile translates into protective and preventive choices. Abstract : Résumé: Les statistiques mondiales sur les grossesses non désirées, les avortements et les IST montrent que les rapports sexuels non protégés sont très fréquents. Il faut faire davantage pour offrir aux femmes et aux hommes un choix élargi de bonnes options de protection. Pour répondre à ce besoin, les activités internationales privilégient l'élaboration de technologies de prévention polyvalentes qui correspondent simultanément à deux indications ou plus. Ces technologies auraient de nets avantages sur les produits à indication unique. Elles comprennent notamment les nouvelles méthodes barrières, les médicaments administrés comme pilules orales ou gels vaginaux/rectaux, les médicaments utilisés en association avec des dispositifs médicaux et des organismes issus du génie génétique qui sécrètent des substances antimicrobiennes. Pour illustrer les progrès dans ce domaine, l'article décrit un gel vaginal contraceptif/antimicrobien à la demande, Amphora (connu précédemment sous le nom d'Acidform) qui en est à un stade avancé de développement. Des essais cliniques sont actuellement prévus pour déterminer si le profil antimicrobien prometteur de ce produit se traduit en choix protecteurs et préventifs. Abstract : Resumen: Las estadísticas mundiales sobre embarazos no planeados, abortos e ITS muestran que el sexo sin protección aún es practicado comúnmente. Falta mucho por hacer para ofrecer a mujeres y hombres una gama más amplia de opciones convenientes de protección. Para satisfacer esta necesidad, los esfuerzos internacionales se están enfocando en crear tecnologías de prevención con múltiples propósitos (MPT), que aborden dos o más indicaciones simultáneamente. Estas tecnologías tendrían significativas ventajas sobre productos con una sola indicación. Ejemplos son los métodos de barrera novedosos inter alia, medicamentos administrados ya sea como tabletas orales o jaleas vaginales/rectales, medicamentos utilizados en combinación con dispositivos médicos y organismos modificados genéticamente, que secretan sustancias antimicrobianas. Como ejemplo de los avances en el campo de MPT, este artículo describe una jalea vaginal anticonceptiva/antimicrobiana en demanda, Amphora (anteriormente conocida como Acidform), ahora en una etapa avanzada de su desarrollo. Actualmente se están planificando ensayos clínicos para averiguar si el prometedor perfil antimicrobiano de este producto ofrece opciones de protección y prevención.